Activist Unbelief in Canadian History. (14th December 2018) - Hanowski, Elliot
Canada has a long history of religious unbelief. This paper offers a social historical survey of its organized, activist forms. The radical thought of the Enlightenment was imported in the late eighteenth century, which saw Voltairean deists like Fleury Mesplet criticizing the Catholic Church in the French-speaking colony of Lower Canada. A long tradition of anticlericalism followed in Quebec even though (or because) the Church was massively influential. The rest of Canada saw freethought and rationalist movements, often organized by working-class autodidacts, developing in the nineteenth century with American and British influences. This tradition continued into the first half of the twentieth century when secularists grappled with fundamentalism and the challenge of radical politics. After World War II the language of secular humanism was deployed and organizations were run by highly educated professionals instead. The position of activist unbelief began to change as Canada shifted from being one of the Western world's most religious countries to being one of the least in the latter half of the twentieth century. Unbelief became unremarkable, though the persistence of religion meant that the twenty-first century saw a revival of militant atheism. This survey shows that unbelief was never just a pure philosophical position but has always been shaped by the social status quo it evolved in or was opposing. Nor was opposition ever enough; activist unbelievers inevitably had to offer the undecided a vision of the secular world they were working towards, and this meant getting involved in some form of politics.